Paired β-sheet structure of an Aβ(1-40) amyloid fibril revealed by electron microscopy - Sachse, Carsten (National Academy of Sciences, 2008)
Alzheimer's disease is a neurodegenerative disorder that is characterized by the cerebral deposition of amyloid fibrils formed by Aβ peptide. Despite their prevalence in Alzheimer's and other neurodegenerative diseases, important details of the structure of amyloid fibrils remain unknown. Here, we present a three-dimensional structure of a mature amyloid fibril formed by Aβ(1-40) peptide, determined by electron cryomicroscopy at ≈8-Å resolution. The fibril consists of two protofilaments, each containing ≈5-nm-long regions of β-sheet structure. A local twofold symmetry within each region suggests that pairs of β-sheets are formed from equivalent parts of two Aβ(1-40) peptides contained in each protofilament. The pairing occurs via tightly packed interfaces, reminiscent of recently reported steric zipper structures. However, unlike these previous structures, the β-sheet pairing is observed within an amyloid fibril and includes significantly longer amino acid sequences.